Pengaruh Profitabilitas, Likuiditas, Dan Aktivitas Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Interverning Pada Perusahaan Sektor Properti Dan Real Estate Yang Terdaftar Di Bei Tahun 2018-2022 - Esther Tioma Nauly Pardede; Hwihanus Hwihanus (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Institutional Benefits determine the current state of affairs within the institution. The existence of good work process results can influence the possibility of financing supporters to provide financing. Institutional benefits can be influenced by several factors such as profitability, liquidity, activity, and Capital Structure. The aim of this exploration is to find out the relationship between Profitability, Liquidity and Action on Company Value where Capital Structure is known as an Interverning variable in Property and real estate institutions listed on the Indonesia Stock Exchange for the 2018-2022 period. This exploration uses quantitative methods. The test method uses secondary data, namely certain financial reports obtained from institutional annual reports or periodic reports that have been evaluated on the IDX for the 2018-2022 period via the authority website www.idx.co.id. There are 21 property and real estate institutions listed on the Indonesian Stock Exchange and 6 institutions were selected to be included as examples over a period of 5 periods, so that in total the samples used are known to be 30 pieces of information that will be considered. The information checking technique uses a Structural Equation Model (SEM) using Partial Least Square (PLS). Research results show that capital structure has a positive and significant effect on company value